Design, synthesis, and structure-activity relationships of new benzofuro[3, 2-b]pyridin-7-ols as DNA topoisomerase II inhibitors. Issue 4 (15th February 2018) - Shrestha, Aarajana; Jo, Hyunji; Kwon, Youngjoo; Lee, Eung-Seok
Graphical abstract: Abstract: Human DNA topoisomerases have become attractive targets for developing more effective anticancer drugs. In this study, a series of new benzofuro[3, 2- b ]pyridin-7-ols were designed and synthesized for the first time and screened for their topoisomerase I and II inhibitory and antiproliferative activity. Structure-activity relationships revealed the position of ortho - and para -hydroxyl group at 2-phenyl ring, and meta -hydroxyl group at 4-phenyl ring of benzofuro[3, 2- b ]pyridin-7-ol are important for potent and selective topo II inhibitory activity. Compound11 showed the most selective and potent topo II inhibition (100% inhibition at 100 µM) and strongest antiproliferative activity (IC50 = 0.86 µM) than all the positive controls in HeLa cell line.